Board Gender Diversity: Challenges and Implications for Corporations in the East African Community. Issue 2 (3rd April 2019) - Mori, Neema; Richard, Evelyn
ABSTRACT: East African Community's (EAC) corporations are required to follow a regional treaty of mainstreaming gender equality. This article discusses challenges encountered by corporate boards of the EAC's corporations when adding women. Agency and resource dependence theories led the study, while a review of the literature was the methodology. We discuss the benefits of diverse boards and challenges faced when developing this diversity. We show how power distance, masculinity, and certainty avoidance prevent women from corporate boards. Furthermore, we discuss how social orientation and business environment impact women's participation. The article discusses various strategies to be considered for increasing diversity.